Bronchoalveolar fluid and plasma inflammatory biomarkers in contemporary ARDS patients. (19th May 2019) - Stapleton, Renee D.; Suratt, Benjamin T.; Neff, Margaret J.; Wurfel, Mark M.; Ware, Lorraine B.; Ruzinski, John T.; Caldwell, Ellen; Hallstrand, Teal S.; Parsons, Polly E.
Abstract: Purpose: Bronchoalveolar fluid (BALF) and plasma biomarkers are often endpoints in early phase randomized trials (RCTs) in acute respiratory distress syndrome (ARDS). With ARDS mortality decreasing, we analyzed baseline biomarkers in samples from contemporary ARDS patients participating in a prior RCT and compared these to historical controls. Materials and methods: Ninety ARDS adult patients enrolled in the parent trial. BALF and blood were collected at baseline, day 4 ± 1, and day 8 ± 1. Interleukins-8/-6/-1β/-1 receptor antagonist/-10; granulocyte colony stimulating factor; monocyte chemotactic protein-1; tumour necrosis factor-α; surfactant protein-D; von Willebrand factor; leukotriene B4 ; receptor for advanced glycosylation end products; soluble Fas ligand; and neutrophil counts were measured. Results: Compared to historical measurements, our values were generally substantially lower, despite our participants being similar to historical controls. For example, our BALF IL-8 and plasma IL-6 were notably lower than in a 1999 RCT of low tidal volume ventilation and a 2007 biomarker study, respectively. Conclusions: Baseline biomarker levels in current ARDS patients are substantially lower than 6–20 years before collection of these samples. These findings, whether from ICU care changes resulting in less inflammation or from variation in assay techniques over time, have important implications for design of future RCTs with biomarkers as endpoints.